2003
DOI: 10.1108/02602280310468215
|View full text |Cite
|
Sign up to set email alerts
|

Wireless – introducing wireless proximity switches

Abstract: Sensors and actuators are found in large numbers on every production line in every industry. And each and every one of them requires data and power cabling. Not only are these cables costly to install, they are also a frequent source of failure. ABB is introducing a novel wireless proximity switch that incorporates a communication module for the power supply, signal transmission and man‐machine communication, and so has no need for cables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The research by Lee Danisch, Kevin Englehart and Andrew Trivett [10] describes shape tape, a thin array of fiber optic curvature sensors laminated on a ribbon substrate, arrange to sense bend and twist. Wireless proximity switches that incorporates a communication module for the power supply, signal transmission and man-machine communication is introduced by Christoffer Apneseth et.all [11]. Gojko Nikolic and Goran Cubric [12] pursue the research of different types of sensors suitable of positioning edge accuracy of textile material since the problem of accurate product positioning on machines for clothing production is more complex than similar problems in other fields of production and installation because of the type of material that is used.…”
Section: B Electro-hydraulic Actuator Systemmentioning
confidence: 99%
“…The research by Lee Danisch, Kevin Englehart and Andrew Trivett [10] describes shape tape, a thin array of fiber optic curvature sensors laminated on a ribbon substrate, arrange to sense bend and twist. Wireless proximity switches that incorporates a communication module for the power supply, signal transmission and man-machine communication is introduced by Christoffer Apneseth et.all [11]. Gojko Nikolic and Goran Cubric [12] pursue the research of different types of sensors suitable of positioning edge accuracy of textile material since the problem of accurate product positioning on machines for clothing production is more complex than similar problems in other fields of production and installation because of the type of material that is used.…”
Section: B Electro-hydraulic Actuator Systemmentioning
confidence: 99%
“…ABB now has a solution to the cabling problem, the wireless proximity sensor (Plate 3), developed by its research teams in Norway, Germany and Switzerland (Apneseth et al, 2002) and demonstrated publicly for the first time in the UK at the Open Days.…”
Section: Wireless Switchingmentioning
confidence: 99%
“…1. In a CET system is used electromagnetic waves, electric field [3,6], light [5,15], and in acoustic waves (ultrasonic) [4] as the "medium" of transfer. Among the most demanding implications, the core of contactless energy transfer CET systems is the characterized in terms of physical isolation between source and load by transformer as inductive, which is dominantly dependent on inductive coupling coefficient [7] between power source and load, and high frequency switching for power electronic converter for energy flow control [8].…”
Section: Introductionmentioning
confidence: 99%